Structural insights of an LCP protein–LytR–from Streptococcus dysgalactiae subs. dysgalactiae through biophysical and in silico methods - Paquete-Ferreira, João; Freire, Filipe; Fernandes, Henrique S.; Muthukumaran, Jayaraman; Ramos, João; Bryton, Joana; Panjkovich, Alejandro; Svergun, Dmitri; Santos, Marino F. A.; Correia, Márcia A. S.; Fernandes, Alexandra R.; Romão, Maria João; et al. (Frontiers in Chemistry, 2024)
The rise of antibiotic-resistant bacterial strains in recent years has become a growing concern and one of the most urgent health problems that needs to be addressed. According to the World Health Organization, only a few new antibiotics reach the market each year, highlighting the need to identify novel therapeutic targets. The LytR-CpsA-Psr (LCP) family of proteins has garnered attention due to its involvement in the insertion of cell wall glycopolymers (CWGPs), such as teichoic acids, into the peptidoglycan. This family of proteins emerges as an interesting target for the development of new antibiotics since their activity occurs in the bacterial cell envelope. Furthermore, CWGPs inserted by LCP proteins play a pivotal role in bacterial adhesion to tissues and surfaces which is an essential stage in bacterial biofilm formation. This study focuses on structural and functional analysis of the LCP domain of LytR from Streptococcus dysgalactiae subsp. dysgalactiae. The structure was solved at 2.80 Å resolution revealing a fold highly similar to homologous proteins. Analysis of the SAXS data indicated putative conformational differences between free and ligand-bound forms of the LytR LCP, suggesting that the protein may adopt a more compact conformation during catalysis upon ligand binding. Additionally, docking and MD simulations predicted the ability of this protein to interact with ADP and ATP and catalyze its conversion to AMP. Experimental validation of these findings was performed through malachite activity assays. These findings provide new insights into the structural features and functional versatility of the LCP domain, paving the way for the design of targeted therapies against antibiotic-resistant bacteria and offering potential strategies for disrupting bacterial biofilm formation.